Clinical concentrations of peroxidases cause dysbiosis in in vitro oral biofilms. (8th March 2018) - Herrero, E.R.; Boon, N.; Bernaerts, K.; Slomka, V.; Verspecht, T.; Quirynen, M.; Teughels, W.
Abstract : Background and Objective: Little is known about the initiation of dysbiosis in oral biofilms, a topic of prime importance for understanding the etiology of, and preventing, periodontitis. The aim of this study was to evaluate the effect of different concentrations of crevicular and salivary peroxidase and catalase on dysbiosis in multispecies biofilms in vitro. Material and Methods: The spotting technique was used to identify the effect of different concentrations of myeloperoxidase, lactoperoxidase, erythrocyte catalase, and horseradish peroxidase in salivary and crevicular fluid on the inhibitory effect of commensals on pathobiont growth. Vitality–quantitative real‐time PCR was performed to quantify the dysbiotic effect of the peroxidases (adjusted to concentrations found in periodontal health, gingivitis, and periodontitis) on multispecies microbial communities. Results: Agar plate and multispecies ecology experiments showed that production of hydrogen peroxide (H2 O2 ) by commensal bacteria decreases pathobiont growth and colonization. Peroxidases at concentrations found in crevicular fluid and saliva neutralized this inhibitory effect. In multispecies communities, myeloperoxidase, at the crevicular fluid concentrations found in periodontitis, resulted in a 1‐3 Log increase in pathobionts when compared with the crevicular fluid concentrations found in periodontal health. The effect of salivary lactoperoxidase and salivary myeloperoxidase concentrations was, in general, similar to the effect of crevicular myeloperoxidase concentrations. Conclusions: Commensal species suppress pathobionts by producing H2 O2 . Catalase and peroxidases, at clinically relevant concentrations, can neutralize this effect and thereby can contribute to dysbiosis by allowing the outgrowth of pathobionts.